2011
DOI: 10.5761/atcs.cr.09.01492
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Infarct Exclusion Repair of Posterior Postinfarction Ventricular Perforation: Triple-patch Technique for Postinfarction Ventricular Septal Perforation in 2 Female Patients

Abstract: We describe a new technique for the early surgical repair of a posterior postinfarction ventricular septal perforation (VSP) in two consecutive female patients. The occurrence of a posterior VSP is rare, and its repair is technically difficult because the posteromedial papillary muscle is located adjacent to the intraventricular septum. This modification appears to prevent leaks to the right ventricle through the VPS with a single direct patch and the use of two equine pericardial patches to form a single endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…After surgeries, all patients recovered from shock and the During the 2000s, some surgeons combined an infarct exclusion technique and a double patch technique, [11][12][13] and we have done the same. Sugimoto, et al 13) have reported such a technique using three pericardial patches, which was performed successfully for not only anterior but also posterior VSP. The combination of both the techniques is thought to be an ideal strategy for acute VSP, although further experience is needed to verify its efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After surgeries, all patients recovered from shock and the During the 2000s, some surgeons combined an infarct exclusion technique and a double patch technique, [11][12][13] and we have done the same. Sugimoto, et al 13) have reported such a technique using three pericardial patches, which was performed successfully for not only anterior but also posterior VSP. The combination of both the techniques is thought to be an ideal strategy for acute VSP, although further experience is needed to verify its efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…The latter were made from large bovine pericardium and sewed into a cylindrical state first, and then later sewed up into a conic state. Sugimoto, et al 13) had devised two pericardial patches to create such a three-dimensional pouch. In the first case (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many biological and biosynthetic materials have been already studied as replacement of the abdominal wall 15 . Although routinely used in cardiothoracic and vascular surgery, neurosurgery, plastic surgery and orthopaedics [20][21][22][23][24][25][26][27]40,41 , equine pericardium has never been employed in bridging repair of the abdominal wall, perhaps because of described complications in other fields of employment likely related to host tissue reactions leading to degradation and leak 24 or fibrosis and shrinkage 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The first experimental report about the use of the equine pericardium dates back to about forty years ago 20 . Since then, it has been used mainly in cardiothoracic and vascular surgery 21,22 , but also in neurosurgery 23,24 , orthopaedics 25 and plastic surgery 26,27 . A literature survey did not reveal studies devoted to the use of equine pericardium in the abdominal wall repair.…”
mentioning
confidence: 99%
“…We adopted the double patch technique in 6 cases (85.7%) 30,31 (vide Figure No.2) and an extra patch in I case (concomitant repair of the LV aneurysm). The incidence of post-operative residual shunt was 0% comparable to the incidence of 24 to 26% described in other series in which a variety of techniques were used.…”
Section: Techniques Of Patch Closurementioning
confidence: 99%